Solution Of Lr-Fuzzy Linear Systemwith Trapezoidal Fuzzy Numberusing Matrix Theory - Ahmad, Nazihah; Malkawi, Ghassan; Ibrahim, Haslinda (Asian Research Publishing Network (ARPN), 2016)
This study provides solutions to aLR-fuzzy linear system (LR-FLS) with trapezoidal fuzzy number using matrix theory. The components of the LR-FLS are represented in block matrices and vectors to produce an equivalent linear system. Then, the solution can be obtained using any classical linear system, such as an inversion matrix. In this method, fuzzy operations are not required and the solution obtained is either fuzzy or non-fuzzy exact solution. Finally, several examples are given to illustrate the ability of the proposed method